2019
DOI: 10.1016/j.engstruct.2019.109467
|View full text |Cite
|
Sign up to set email alerts
|

Seismic shear and acceleration demands in multi-storey cross-laminated timber buildings

Abstract: A realistic estimation of seismic shear demands is essential for the design and assessment of multi-storey buildings and for ensuring the activation of ductile failure modes during strong ground-motion. Likewise, the evaluation of seismic floor accelerations is fundamental to the appraisal of damage to non-structural elements and building contents. Given the relative novelty of tall timber buildings and their increasing popularity, a rigorous evaluation of their shear and acceleration demands is all the more c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Moreover, previous analytical studies have demonstrated that higher vibration modes can be coupled with the rocking motion and excited by the forces generated during impact, regardless of the frequency of the excitation [26]. This behaviour has been experimentally observed in steel rocking structures [27], it has been predicted to occur also in rocking timber structures, albeit with lower amplitudes due to their typically softer set down [28] and was speculated to lie behind some of the large peak acceleration amplifications anticipated in multi-storey panellized timber buildings with rocking motion components [29]. Wiebe and Christopolous examined the alternative of using multiple rocking sections over the height of a base-rocking system, thus allowing the designer to control the higher mode amplification of moments above the base of the wall [25].…”
Section: Introductionmentioning
confidence: 84%
“…Moreover, previous analytical studies have demonstrated that higher vibration modes can be coupled with the rocking motion and excited by the forces generated during impact, regardless of the frequency of the excitation [26]. This behaviour has been experimentally observed in steel rocking structures [27], it has been predicted to occur also in rocking timber structures, albeit with lower amplitudes due to their typically softer set down [28] and was speculated to lie behind some of the large peak acceleration amplifications anticipated in multi-storey panellized timber buildings with rocking motion components [29]. Wiebe and Christopolous examined the alternative of using multiple rocking sections over the height of a base-rocking system, thus allowing the designer to control the higher mode amplification of moments above the base of the wall [25].…”
Section: Introductionmentioning
confidence: 84%
“…Since the 1990s, the University of Graz has been one of the first institutions to undertake numerous international CLT research activities. Further, more complete and elaborated studies were carried out in the 2000s, on dimensional stability and stiffness [35] and the adequate connections for a high dissipation capacity: Ceccotti et al proposed a simplified method for the determination of the seismic behavior factor "q" of timber buildings [26], that measures a relative energy loss per oscillation cycle; Sustersic et al investigated the seismic analysis of multi-story cross-laminated timber buildings [29]; Gavric et al proposed an extended experimental program on typical cross-laminated panels connections [36]; Demirci et al investigated the scaling of seismic shear and acceleration demands in multi-story cross-laminated timber buildings and its dependency on various structural properties [37]; Sustersic et al worked with the issue of seismic retrofit and thermal insulation improvement of existing buildings with CLT technology [38].…”
Section: Overview On Basic Research On Clt Systemsmentioning
confidence: 99%
“…It is also possible to build multi-story buildings, making the construction system in CLT attractive from the economic point of view and from the environmental perspective thanks to a reduced exploitation of the soil [26,37,101,102].…”
Section: Characteristic Properties Of Clt Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same modelling strategy outlined in the previous section was adopted while the position, dimension, type, and number of connectors between adjacent walls and slabs were obtained from Dujic et al, and Rinaldin and Fragiacomo . Other dynamic properties of the building were also well predicted by the OpenSees model developed() including an 8% difference in natural periods and a close estimation of peak accelerations (eg, 2.61g against 2.52g at the top floor for the experimental and numerical model, respectively). Notably, despite the simplifications, a maximum total cumulative difference of just over 7% was observed, and a good match in the temporal evolution of energy dissipation was attained (Figure 6G).…”
Section: Seismic Design and Modelling Assumptionsmentioning
confidence: 99%